Impact of Surgery on Survival in Stage IV Breast Cancer. Issue 6 (26th August 2016) - AlJohani, Badria; AlMalik, Osama; Anwar, Ehab; Tulbah, Asma; Alshabanah, Mohamed; AlSyaed, Adher; Ajarim, Dahish; ALTweigeri, Taher
Abstract: We aimed to assess retrospectively the survival outcome in patients with stage IV breast cancer who underwent surgery. In a retrospective, nonrandomized study of stage IV breast cancer patients diagnosed in a single institution between 2000 and 2012, we assessed patient's survival in the context of baseline characteristics. A total 678 patients with metastatic breast cancer were included; 412 (60.77%) underwent surgery for the primary tumor (Surgery group), and 266 (39%) did not underwent surgery for the primary tumor (Nonsurgery group), with a median follow‐up of 41 months. Patients in the Surgery group had longer survival (41 versus 27 months, p < 0.0029). The 5‐year survival rate for Surgery group was 34% compared with 14% for the Nonsurgery group. A multivariate analysis revealed surgery (p = 0.0003), large tumor size (p = 0.0195), ER‐positive (p < 0.0001), and metastasis at presentation (p = 0.0032) were prognostic variables. Loco‐regional surgery does confer a survival advantage in stage IV breast cancer, however, selection bias cannot be excluded, a well‐designed and powerful randomized, controlled trial would be valuable to answer whether surgery can improve survival.